An overview of the transboundary dust events in southeastern Turkmenistan near the border of Iran (Sarakhs-Badkhyz region) - Mohammad Reza Mansouri Daneshvar; Seyed Javad Rasouli; Aliasghar Dehqanpour Aliaqa (Environmental Systems Research)
Abstract This paper revealed the intensifying transboundary dust events in southeastern Turkmenistan near the border of Iran, using long-term spatial and statistical data (1980–2023). This study introduced the definition of a new source of dust storms, which is called the Sarakhs-Badkhyz region, apart from the Karakum and Kyzylkum deserts. The mentioned dust source with a surface area of 100,000 km2 is located in southeastern Turkmenistan and northeastern Iran. The remotely sensed investigation of this study was supported with local and international re-analyzed datasets (e.g., IRIMO, Eumetsat, and NASA). A drastic temperature increase triggers evaporation and also dryness of the sandy deserts in southeastern Turkmenistan. Then, dried sandy grounds and high wind speeds are important factors in creating favorable conditions for dust storm formation. Additionally, the increase in the intensity of general atmospheric circulation and the more energetic activity of the frontal cyclones, associated with the cold air intrusion of the Siberian anticyclone, are important mechanisms in the dust events of the study area. The decrease in precipitation in recent years in addition to declining the water flows of the Tejen and Murghab rivers from their basins is the reason for the dryness of the sandy ground of the Sarakhs-Badkhyz region. As a result, the defined region is a susceptible zone to source sediments of dust storms in the Middle East. Future research should analyze the possible effects of the dust storms, raised from the Sarakhs-Badkhyz region, on the cultivation, construction, immigration, and healthcare situations of the inhabitants and settlements, dominantly in Mashhad, Mary, and Herat urban regions (with a total of 4.35 million inhabitants).